Quality improvement in pre-hospital critical care: increased value through research and publication - Rehn, Marius (BioMed Central, 2014)
Pre-hospital critical care is considered to be a complex intervention with a weak evidence base. In quality improvement literature, the value equation has been used to depict the inevitable relationship between resources expenditure and quality. Increased value of pre-hospital critical care involves moving a system from quality assurance to quality improvement. Agreed quality indicators can be integrated in existing quality improvement and complex intervention methodology. A QI system for pre-hospital critical care includes leadership involvement, multi-disciplinary buy-in, data collection infrastructure and long-term commitment. Further, integrating process control with governance systems allows evidence-based change of practice and publishing of results.